The dirty south [videorecording (DVD)] - Yerby, Matthew; Vogel, Andrew (Producer); Petrongolo, Suzann Toni; Holland, Willa, 1991-; West, Shane; Péré, Wayne; Hayes, Billy (Actor); Quinney, Caleb; Valentin, Gissette; Cayouette, Laura, 1964-; Manning, Mike C., 1987-; Mulroney, Dermot; et al. (Cineverse, 2023)
Sue Parker finds herself in a desperate battle to save her family's struggling business, which is on the brink of collapse due to her father's neglect. When a handsome drifter comes into town she sees him as the only chance to prevent their bar from falling into the hands of a ruthless local tycoon. What starts as a simple plan to save her family, quickly spirals into larceny, lawlessness, and deadly consequences.